2018
DOI: 10.1113/jp275001
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent hypoxia with concurrent hypercapnia evokes P2X and TRPV1 receptor‐dependent sensory long‐term facilitation in naïve carotid bodies

Abstract: Apnoeas constitute an acute existential threat to neonates and adults. In large part, this threat is detected by the carotid bodies, which are the primary peripheral chemoreceptors, and is combatted by arousal and acute cardiorespiratory responses, including increased sympathetic output. Similar responses occur with repeated apnoeas but they continue beyond the last apnoea and can persist for hours [i.e. ventilatory and sympathetic long-term facilitation (LTF)]. These long-term effects may be adaptive during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 66 publications
3
56
0
Order By: Relevance
“…Furthermore, losartan application in superfused CBs effectively prevents the sensory facilitation caused by intermittent hypercapnic hypoxia but does not reverse this effect when applied afterwards (Roy et al . ). This evidence suggests that Ang II surges and AT 1 R activation during intermittent hypoxia activate a cascade of signalling that is subsequently insensitive to acute AT 1 R blockade.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, losartan application in superfused CBs effectively prevents the sensory facilitation caused by intermittent hypercapnic hypoxia but does not reverse this effect when applied afterwards (Roy et al . ). This evidence suggests that Ang II surges and AT 1 R activation during intermittent hypoxia activate a cascade of signalling that is subsequently insensitive to acute AT 1 R blockade.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, inhibition of protein kinase C (PKC) showed that the phosphorylation mediated by this protein is a key factor in both induction and maintenance of sLTF (Roy et al . ).…”
mentioning
confidence: 97%
“…Roy et al . () used the well‐accepted ex‐vivo carotid body – CSN preparation, which keeps the perfusion pressure, temperature and pH in the carotid bifurcation comparable with that in whole animals. They also used an in‐vivo anaesthetized rat preparation to evaluate the role of TRPV1 receptors in sympathetic sLTF.…”
mentioning
confidence: 99%
See 2 more Smart Citations